Elasticsearch blueprints : a practical project-based guide to generating compelling search solutions using the dynamic and powerful features of Elasticsearch /: a practical project-based guide to generating compelling search solutions using the dynamic and powerful features of Elasticsearch. (2015) - Mohan, Vinoth Mohan, 1983-
No abstract available